A meta-analysis for Lianhua Qingwen on the treatment of Coronavirus disease 2019 (COVID-19) - Jieqin Zhuang; Xingzhen Dai; Qihua Wu; Hairong Cai; Xue Fu; Weizhang Zhang; Bojun Chen (Elsevier, 2021)
Background: Traditional Chinese medicine (TCM) has been proven to played a great important role on the treatment of COVID-19. As one of the drugs recommended in Chinese guidelines, Lianhua Qingwen Granules or Capsules (LQ) are widely used.This systematic review and meta-analysis amis to evaluate the clinical efficacy of LQ on the treatment of COVID-19. Methods: Seven databases (PubMed, EMBASE, CENTRAL, CNKI, VIP, CBM and Wanfang) were searched to include all appropriate clinical trials that explore the efficacy of LQ on the treatment of COVID-19. Result: A total of 3 trials including 245 COVID-19 patients were eventually enrolled.Compared with the control group,the LQ group showed great significant difference on reducing the rate of clinical change to severe or critical condition[RR = 0.38, 95 %CI (0.17,0.85), P < 0.05]and the fever time (SMD =-0.57,95 %CI (-0.96,-0.17), P<0.05),as well as the significant improvement on the disappearance rate of the clinical symptoms: fever [RR = 1.36,95 %CI (1.14,1.61), P < 0.05],cough[RR = 1.99,95 %CI (1.39,2.86), P < 0.05],fatigue[RR = 1.52,95 %CI (1.15,2.01), P < 0.05] and anhelation [RR = 4.18,95 %CI (1.99,8.81), P < 0.05], but no significance on expectoration[RR = 2.46,95 %CI (0.81,7.51), P < 0.05]. Conclusion: The clinical application of LQ on the treatment of COVID-19 has significant efficacy in improving clinical symptoms and reducing the rate of clinical change to severe or critical condition. Nevertheless, due to the limited quantity and quality of the included studies, more and higher quality trials with more observational indicators are expected to be published.